PERBANDINGAN HASIL INVESTIGASI PENYEBAB INSIDEN DENGAN MENGGUNAKAN METODE SCAT DAN METODE TRIPOD (STUDI KASUS PENYEBAB INSIDEN DI TERMINAL LPG SEMARANG) - Miranti Miranti; Hanifa Maher Denny; Bina Kurniawan (Jurnal Kesehatan Masyarakat (Undip), 2018)
Incidents are event that result in an accident or a near-miss event. The cause of the incidence can be found by incident investigation methods to prevent future incidents ought to be the same. Terminal LPG Semarang (TLS) is a company with high hazard potential. TLS uses SCAT to investigate the cause of incident. SCAT is a secondary method that identify the problem at the management and safety culture so operational and human error factors are not identified. Tripod is a primary method that identify the problem on organizational, operational, and human error factors. This descriptive research aims to describe the comparison of incident cause investigation results using SCAT and Tripod method. Data obtained using the technique of in depth interview and secondary data collection. The main informants in this study were 14 workers involved in the incident. The triangulation informant is a 4 person investigators who investigate the incidents. The result showed that there is equation of result in identification of immediate cause between SCAT method and Tripod method but there is difference of result in identification of barrier, precondition, underlying cause, and recommendation between SCAT method and Tripod method. From these results the company is expected to conduct in depth analysis of appropriate incident investigation methods for the company.